Studies on the role of Rosa roxburghii Tratt quercetin in improving intestinal metabolism and the microbiome in mice with Alzheimer's disease - Tingyuan Ren; Zhen Chen; Jiao Xie; Shuming Tan; Yuping Zhu (Journal of Functional Foods, 2024)
To explore the possible pathways and biomarkers of the influence of Rosa roxburghii Tratt (RRT) quercetin on intestinal microbiota and its metabolites in the pathogenesis of Alzheimer’s disease (AD), the experiment was divided into normal control (NC) group, model (MC) group, high-dose RRT quercetin (HG) group, low-dose RRT quercetin (LG) group and galantamine hydrobromide (Gal) group. The levels of acetylcholine (Ach), acetylcholinesterase (AChE) and choline acetyl transferase (ChAT) in brain tissue were measured. The changes in the microbiome and metabolites in the cecum contents were identified by 16S rRNA gene amplicon sequencing and UPLC/HRMS, respectively. The results showed that RRT quercetin increased the levels of Ach and ChAT in the brain and decreased AChE activity in the brain. The diversity of the intestinal microbiome of AD mice was significantly improved by RRT quercetin. The results showed that RRT quercetin regulates the intestinal microenvironment, intestinal microbiome and metabolites to improve cognitive function in AD mice.